2013
DOI: 10.1172/jci60415
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell–specific serine palmitoyltransferase subunit 2 haploinsufficiency reduces murine atherosclerosis

Abstract: Serine palmitoyltransferase (SPT) is the first and rate-limiting enzyme of the de novo biosynthetic pathway of sphingomyelin (SM). Both SPT and SM have been implicated in the pathogenesis of atherosclerosis, the development of which is driven by macrophages; however, the role of SPT in macrophage-mediated atherogenesis is unknown. To address this issue, we have analyzed macrophage inflammatory responses and reverse cholesterol transport, 2 key mediators of atherogenesis, in SPT subunit 2-haploinsufficient (Spt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 69 publications
(75 reference statements)
2
35
0
1
Order By: Relevance
“…5D). Second, when we genetically eliminated p38α in macrophages with the LysM-Cre deleter (p38α ΔM ) as previously reported (30), we observed negligible depletion of p38α amounts, arguing conclusions drawn using this deleter system are difficult to interpret (Fig. 5E,F).…”
Section: Resultssupporting
confidence: 49%
“…5D). Second, when we genetically eliminated p38α in macrophages with the LysM-Cre deleter (p38α ΔM ) as previously reported (30), we observed negligible depletion of p38α amounts, arguing conclusions drawn using this deleter system are difficult to interpret (Fig. 5E,F).…”
Section: Resultssupporting
confidence: 49%
“…In SM-depleted mutant CHO cells, ABCA1-mediated cholesterol efflux was increased without altering the cell surface or total ABCA1 levels (50). Also, a genetic lowering of macrophage SM via a different subunit of serine palmitoyltransferease (Sptlc2-hemizygous mice) was also reported to increase the ABCA1-dependent cholesterol efflux to apoAI in cholesterol-loaded cells, associated with a decrease in SPT1 protein and an increase in total ABCA1 protein levels (51). Meanwhile Ghering and Davidson (40) reported that the addition of a short chain ceramide analog to ABCA1 expressing cells increases ABCA1 levels and cholesterol efflux to apoAI, whereas physiological ceramides had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ACSL isoforms expressed in macrophages, ACSL1, is markedly upregulated by inflammatory mediators and is required for atherosclerosis in diabetic mice 64 . Moreover, macrophages deficient in serine palmitoyltransferase subunit 2 (SPT) exhibit reduced levels of sphingomyelin in lipid rafts, which results in reduced TLR4 activity and reduced atherosclerosis 65 . Fatty acids might promote inflammatory processes by several different mechanisms, including altered activation of nuclear receptors, altered generation of bioactive lipid mediators, and facilitation of TLR4 activation through organization of TLR4 receptor complexes within lipid raft domains.…”
Section: Homeostatic Imbalance In Intracellular Lipids Metabolites Amentioning
confidence: 99%